Headache after lumbar puncture: randomised crossover trial of 22-gauge versus 25-gauge needles. Issue 3 (14th November 2013) - Crock, Catherine; Orsini, Francesca; Lee, Katherine J; Phillips, Roderic J
Abstract : Objectives: To compare the frequency of headache and the procedure time following lumbar puncture (LP) using a 25-gauge needle compared to a 22-gauge needle. Design: 4-period crossover blinded randomised controlled trial. Setting: Oncology unit, Royal Children's Hospital, Melbourne. Patients: Children aged 4–15 years at enrolment having LPs as part of their treatment for leukaemia. Interventions: Each child was allocated a random sequence of four LPs, two with a 22-gauge and two with a 25-gauge needle. Outcome measures: The presence of post-LP headache. Secondary outcomes included the presence of any headache, procedure time and impact of headache on the family. Results: Data on 341 procedures in 93 randomised children were analysed. There was little difference in the incidence of post-LP headache between the two needle sizes (22-gauge 7.2%, 95% CI 3.8 to 12.2; 25-gauge 4.6%, 95% CI 2.0 to 8.9, p=0.3) or in the incidence of any headache (22-gauge 18% 95% CI 12.5 to 24.6; 25-gauge 15%, 95% CI 10.0 to 21.1, p=0.4). Use of the 25-gauge needle was associated with longer procedure times. The incidence of post-LP headache showed little evidence of an age effect (OR =1.1, 95% CI 0.98 to 1.3) and was higher in girls than in boys (11% vs 3%, respectively, OR=3.3, 95% CI 1.3 to 8.4, p=0.014). Fifty-five per cent of families with a child with a post-LP headache assessed the overall functional impact as moderate or severe. Conclusions: There was little difference in the occurrence of post-LP headache or any headache between procedures carried out using the 22-gauge or 25-gauge needles. Depending on the circumstances of the procedure and the experience of the operator, either gauge may be appropriate for an LP in a child.